Classicising crisis
1 online resource (x, 189 pages)
Keywords: "Geopolitical shifts and economic shocks, from the early modern period to the 20th century, were frequently represented in terms of classical antecedents. In this book an international team of contributors - working across classics, history, politics, and English - address a range of revolutionary transformations in England, America, France, Italy, and Russia, all of which were accorded the classical treatment. The chapters investigate discrete cases of classicising crisis, while the introduction highlights patterns among these moments. Underlying the collection is the critical premise that the association of revolutions with the Greco-Roman classics, otherwise quite conventional and familiar, may itself involve an epistemic 'crisis', as these terms are alien to one another, antagonistic, and yoked together in a violent blending of ancient and modern. Classicising crisis: the modern age of revolutions and the Greco-Roman repertoire is essential reading for students and scholars of classical reception and classicism, and will also be of interest to researchers in related subjects"--